Inovasi Bisnis Print On Demand dengan Penerapan Teknologi AI dalam Kelompok BUMNAG untuk Mendorong Technopreneurship di Simalungun: Inovasi Bisnis Print On Demand dengan Penerapan Teknologi AI - Jaya Tata Hardinata; Situmorang, Eduward; Saragih, Reagan Surbakti; Ema Deloris Silaban; Dinda Zefanya Simanjuntak (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service Program (PKM) titled "Innovation in Print on Demand Business with AI Technology Application within BUMNAG Groups to Foster Technopreneurship in Simalungun" aims to enhance the skills and understanding of local communities, especially the youth, in managing technology-based Print On Demand (POD) businesses. AI technology was directly applied in various aspects of the POD business, including the creation of personalized designs using AI-based tools like Canva AI and Adobe Firefly, enabling participants to produce creative and market-relevant designs without prior graphic design experience. The program's outcomes demonstrate the participants' success in producing various creative POD-based products, including custom-designed screen-printed t-shirts, personalized mug presses, wood-transfer images, and unique keychains. The quality of these products meets marketable standards for both local and broader market potential. However, challenges such as limited production equipment and the short training duration remain significant barriers to scaling marketing efforts. Despite these obstacles, the program's positive impact is evident, particularly in enhancing participants' technical skills and raising awareness of the potential of technology-driven businesses. This program successfully promotes local technopreneurship by empowering the community through AI-based innovations. With improved facilities and continuous mentoring, AI-based POD businesses have the potential to become sustainable and competitive drivers of the local economy.